PENEGAKAN HUKUM TERHADAP PELANGGARAN PENGGUNAAN LAMPU ROTATOR BAGI KENDARAAN PRIBADI MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU - Refomeilia maras; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Everyone person in Indonesia who uses a motorized vehicle, one of which is a private vehicle to facilitate their activities and facilitate movement from one place to another. In its development, the automotive industry in the world is increasingly sophisticated and equipped with additional features to modify vehicles such as adding rotator lights to private vehicles. Meanwhile, the use of rotator lights is only for certain vehicles as referred to in Article 59 paragraph (5) of Law Number 22 of 2009 concerning Road Traffic and Transportation. The purpose of writing this thesis: First, to find out how to enforce the law against violations of the use of rotator lights for private vehicles in Pekanbaru City. Second, to find out how the sanctions are given for violations of the use of rotator lights for private vehicles in Pekanbaru City.The type of research used in this legal research is sociological legal research, sociological legal research can be in the form of research that wants to see the relationship between law and society. This research was conducted at the Pekanbaru Police. The data used in this study is primary data, namely data obtained directly through respondents by conducting research in the field and secondary data. Data collection techniques using observation, interviews and questionnaires. Analysis of the data used, the authors obtained qualitative data. In drawing conclusions, the author uses the method of deductive thinking, which is a way of thinking that draws conclusions from a general statement or proposition into a specific statement.From the results of the study, it was found that law enforcement against violations of the use of rotator lights for private vehicles in Pekanbaru City by the Pekanbaru City Police, especially the Pekanbaru City Police Traffic Unit had made maximum efforts by making various efforts starting from pre-ordering, preventive, and repressive efforts, although in the end these violations still occur frequently. Keywords: Law Enforcement - LightsRotator